2013
DOI: 10.3102/0002831213488818
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Academic Achievement Through Career Relevance in the Middle Grades

Abstract: Research and theory suggest that students learn more effectively when they perceive course content as relevant to their futures. The current research assessed the impact of CareerStart, a middle grades instructional strategy designed to advance the occupational relevance of what students are being MICHAEL E. WOOLLEY, PhD, is associate professor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The potential for such an approach is reflected by programmes such as Career Start, which involved incorporating career-relevant instruction into lessons in core subjects (mathematics, English/language arts, science and social studies) during the middle school years. A randomised control trial of this programme indicated that these career-relevant lessons led to higher levels of school engagement and valuing and mathematics attainment (Woolley, Rose, Orthner, Akos, & Jones-Sanpei, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The potential for such an approach is reflected by programmes such as Career Start, which involved incorporating career-relevant instruction into lessons in core subjects (mathematics, English/language arts, science and social studies) during the middle school years. A randomised control trial of this programme indicated that these career-relevant lessons led to higher levels of school engagement and valuing and mathematics attainment (Woolley, Rose, Orthner, Akos, & Jones-Sanpei, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One such initiative is CareerStart Rose et al, 2012;Woolley et al, 2013), which focused on integrating links to jobs in all areas of the middle school curriculum (including science). While it is too soon to explore outcomes around adult participation, this work did find that the intervention had positive results for school valuing and mathematics attainment.…”
Section: Discussionmentioning
confidence: 99%
“…In achieving promotional criteria, it is important to align students higher order thinking and relevance of the content to their real life experiences to increase classroom engagement and eventually academic achievement [11]. Increasing student's awareness of the relevance of learning will assist in improving their problem-solving skills and the realization of how such skills apply to real-world applications [12].…”
Section: Introductionmentioning
confidence: 99%